The Highlands of Central India : Notes on Their Forests and Wild Tribes Natural History and Sports - Forsyth, J., (Brill | Manohar Publishers & Distributors, 2024)
This volume by Forsyth covers the topography, indigenous population, natural ecology, and activities around the Central Highland region, i.e. the area from the Deccan plateau to the Indo-Gangetic plains. The book covers the influx of migrants, the impact of Rajput and Mughal rule under Akbar, history of aborigine communities such as Kols, Bhils, Korkes, Baigas, Gonds, etc. It contains the flora and fauna life in Narbada Valley, Mahadeo Hills, Tapti, Higher Narabada Valley, and Mahanadi regions. Interestingly, the author has provided a vivid description of the customs of native tribes of this region, the deities worshipped by the Central Indian tribes, marital and other societal customs, and the influence of Hinduism, particularly Shaivism. Animals such as, tigers, and elephants, which are found in abundance in this region, are discussed. This book is highly beneficial to anthropologists and sociologists interested in tribal communities and their lives.